2018
DOI: 10.1159/000492851
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Adipose-Derived Stem Cells Promotes VEGF-C-Dependent Lymphangiogenesis by Regulating miRNA-132/TGF-β Pathway

Abstract: Background/Aims: Lymphangiogenesis plays an important role in the pathogenesis of inflammatory bowel diseases (IBD), and vascular endothelial growth factor-C (VEGF-C) is a powerful lymphangiogenic factor. Adipose-derived stem cells (ADSCs) are a promising therapeutic modality for several diseases because ADSCs secret growth factors and exosomes, which modulate hostile microenvironments affected by diseases. However, the effect of exosomes on VEGF-C-dependent lymphangiogenesis and its mechanism remain unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Exosomal miR-let7c attenuated kidney injury by significantly downregulated TGFβ1 and TGFR1 in the kidneys [38]. Exosomal miR-132 promoted lymphangiogenic response by directly targeting Smad-7 and regulating TGF-β/Smad signaling [39]. In the present study, there were 16 genes targeted by 15 differentially expressed microRNAs were involved in TGFβ signaling.…”
Section: Discussionmentioning
confidence: 67%
“…Exosomal miR-let7c attenuated kidney injury by significantly downregulated TGFβ1 and TGFR1 in the kidneys [38]. Exosomal miR-132 promoted lymphangiogenic response by directly targeting Smad-7 and regulating TGF-β/Smad signaling [39]. In the present study, there were 16 genes targeted by 15 differentially expressed microRNAs were involved in TGFβ signaling.…”
Section: Discussionmentioning
confidence: 67%
“…4b, c). These cytokines have been confirmed that they play an essential role in promoting angiogenesis [35, 36]. Through GO enrichment analysis, we found that the biological process of DEPs in the MS+ADSC group was involved in cell migration, cellular component movement, and peptidyl-tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 65%
“…Lymphangiogenesis could facilitate the stabilization of inflammatory cells and resolve tissue edema in acute and chronic inflammatory situations. Similarly, studies also showed that exosomes isolated from adipose-derived stem cells treated with vascular endothelial growth factor-C (VEGF-C) expressed more miRNA-132, which promotes lymphangiogenesis by regulating TGF-β/Smad signaling [66].…”
Section: Adexos Mirnas and Chronic Inflammationmentioning
confidence: 96%